China’s Strategy on the Line of Actual Control: Benefits, Challenges, and Potential Outcomes - Jai Kishan Singh (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
This paper examines why China has chosen to either restore the previous situation or maintain the current one along the disputed Line of Actual Control (LAC), a topic that has not been thoroughly explored in current literature. The analysis indicates that keeping the status quo provides China with various geopolitical, geo-economic, and geostrategic advantages. These benefits include reaffirming its claim line from the 1960s, gaining tactical and strategic leverage along the LAC, ensuring control over Aksai Chin, and hindering India’s rise as a regional and global power. However, this approach also opens the door to potential conflict or war with India, which could jeopardize China’s ambitions of becoming the leading global power, particularly if the outcome is not a clear victory. A loss or stalemate in a conflict with India would harm China’s international reputation and negatively affect the stability and survival of the Communist Party of China (CPC). On the other hand, reverting to the previous status quo presents considerable tactical and strategic disadvantages. It may also pose domestic political risks for President Xi Jinping, potentially undermining his leadership and authority within the country. The dual nature of maintaining the status quo—providing strategic benefits while also risking conflict or political instability—illustrates the intricate calculations that shape China’s stance on the LAC issue. This situation emphasizes the careful balance China must maintain between pursuing its strategic goals and managing risks to its domestic and international reputation .